2023
DOI: 10.1039/d3cp01288c
|View full text |Cite
|
Sign up to set email alerts
|

Frictional properties of MoS2 on a multi-level rough wall under starved lubrication

Abstract: Owing to nano-MoS2’s excellent anti-friction and anti-wear properties, nano-MoS2, which can be acted as a nano-additive in lubricating oil or solid lubricant, is believed to have great potential in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This approach is shown in Fig. 12 c) and has been used at times in the literature for studying different types of lubricants [114,129,405,421,430]. This comes with the drawback that a single event process is studied, which brings difficulties for the sampling of statistically meaningful observables.…”
Section: Computational Tribology On the Atomistic Levelmentioning
confidence: 99%
“…This approach is shown in Fig. 12 c) and has been used at times in the literature for studying different types of lubricants [114,129,405,421,430]. This comes with the drawback that a single event process is studied, which brings difficulties for the sampling of statistically meaningful observables.…”
Section: Computational Tribology On the Atomistic Levelmentioning
confidence: 99%
“…Under the high temperature of the friction surface, these nanoparticles can easily melt or sinter in the microcracks in the contact zone, forming ordered nanoparticles and closely bonding with the friction surface [128]. Yi et al [140] used a molecular dynamics approach to construct rough surfaces and multilevel dimpled structures to simulate oil-poor lubrication before oil film rupture, and the simulation results showed that multilayered MoS 2 acted as a load-bearing agent at light loads or low speeds and went into the grooves to repair the surfaces at heavy loads or high speeds. Yi et al [141] used a solvent/hydrothermal method to prepare MoS 2 particles in three morphologies: flower-like, microspheres, and nanosheets.…”
Section: Other Mechanismsmentioning
confidence: 99%